A CASE REPORT ON AYURVEDIC MANAGEMENT OF VICHARCHIKA (ECZEMA) - Priyadarshan M. Sawant; U.K. Bande (International Journal of Ayurveda and Pharma Research, 2020)
Kushtarog is classified in 2 types i.e., Mahakushta and Kshudrakushta. Vicharchika is described under Kshudrakushta. Vicharchika is the type of Kshudrakushta often encountered by Ayurvedic dermatologists characterized with symptoms, namely, Kandu, Srava, Pidaka and Shyava varna. Vicharchika is often correlated to eczema based on the clinical presentations. The modern science has greatly advanced, particularly in dermatology but there is no specific medication for sure cure of eczema but symptomatic treatments like steroids are used, but they produce serious side effects like nephrotoxicity, osteoporosis, skin cancer etc. Whereas Ayurveda treats from the root of eczema by cleansing vitiated Dosha and balancing the Dosha and Dhatus without any side effects. A 27 years old male patient approached the OPD with the chief complaints of blackish discoloration, itching, flaking, cracking and bleeding over the anterior side of b/l legs. All the complaints were from 8 months. The patient was given completely Ayurvedic treatment with Panchnimbadi vati, Haridra khand, Gandhak rasayan vati and Sukshma triphala vati, Panchnimbadi churna lepa and Jalaukavcharan and the results were remarkably seen and there was significant improvement in the symptoms. Hence this study was taken to prove that Ayurvedic management has remarkable results in Vicharchika (eczema). Observation and results were drawn on the basis of assessment criteria. Discussion was done on the basis of entire observations during research. Conclusion was drawn on the basis of result.